Letter - Miller, L. B.
041-0170-001 Chairman N. MARRA, J.P. Secretary Mrs L.B. MILLER Treasurer WM. HUGHES Telephone No. 4423 Dundee Trades and Labour Council OFFICE: LABOUR HALLS, 48 WELLGATE DUNDEE 27th August 1936 National Labour Party Transport House London Dear Sir enclosed please find cheque £7.0.0 and 10/ paper money being. £2. 10. 0 By-election Fund July 1936 Extracted AW £5. 0. 0. Spainist Medical Fund - Cheque sent to Dr Brook FC £7. 10. 0 yours faithfully (Mrs) L.B. Miller Secretary 292/946/41/170